Thalidomide as a rescue protocol for treatment of multiple myeloma in dogs: preliminary data from a multicentre retrospective study - Ciccarelli, Stefano; Leo, Chiara; Perrone, Chiara; Franchini, Delia; Bonazzi, Irene; Finotello, Riccardo (Frontiers in Veterinary Science, 2026)
Multiple Myeloma (MM) in dogs is typically treated with a combination of alkylating agents and corticosteroids. However, treatment failure or intolerance, often due to cumulative toxicities, can limit the long-term efficacy of these protocols. Thalidomide, an immunomodulatory and anti-angiogenic drug widely used in human MM, remains largely unexplored in veterinary oncology. This study retrospectively evaluated the clinical efficacy and safety of thalidomide as a rescue therapy in dogs with MM that were refractory to or intolerant of standard treatments. Medical records from three referral centers were reviewed, identifying dogs that met the inclusion criteria. All seven selected dogs received melphalan, and four were also treated with cyclophosphamide prior to thalidomide. Thalidomide was administered once daily in all dogs, with one case requiring dose escalation. The median duration of thalidomide administration was 440 days (range: 146–580 days). A complete response was achieved or maintained in five dogs (71%). Adverse events (AEs) were limited to grade II lethargy in two cases, with no hematologic, gastrointestinal, or urinary AEs reported. The median PFS during thalidomide treatment was 490 days (95% CI: 408.7–571.4), while it was 180 days (95% CI: 54.8–305.2) during melphalan therapy. Median overall survival (OS), calculated from diagnosis to last follow-up, was 680 days (95% CI: 542.8–817.2). These findings suggest that thalidomide is a well-tolerated and potentially effective rescue therapy for canine MM, particularly in patients unresponsive to or unable to tolerate conventional chemotherapy. Further prospective studies are warranted to evaluate its efficacy as part of first-line or combined protocols.